Tracking the tail. Issue 2 (3rd September 2020) - Friedlaender, Alex; Liu, Stephen V; Addeo, Alfredo
Abstract : Immune-checkpoint inhibitors have deeply changed the therapeutic landscape of advanced non-small cell lung cancer without actionable genomic alterations. Immune-checkpoint inhibitors have become standard front-line therapy, especially among patients with tumours expressing high levels of programmed death ligand-1; yet, many patients do not respond to therapy. This has led to the adoption of front-line combination therapies, administering programmed death-1 inhibitors concomitantly either with other checkpoint inhibitors, chemotherapy or both. Today's approved standard of care includes options with chemoimmunotherapy or dual checkpoint blockade, but each combination has only been compared to chemotherapy alone and no head-to-head trials exist. In cross-trial comparisons, combinations trials appear to show numerically superior responses to single-agent checkpoint inhibitors but the question is whether they ultimately offer a survival advantage. In this manuscript, we summarize and analyse all currently available front-line immune-checkpoint inhibitor trials in non-small cell lung cancer, whether as monotherapy or in combination with chemotherapy, second immunotherapy agents or both. Should standards of care change given the current data? While we ponder this question, we illustrate current data and conclude that the answer lies in tracking the tail of the survival curves.